Polygenic risk scores for Alzheimer's disease are related to dementia risk in APOE ɛ4 negatives. Issue 1 (22nd January 2021) - Najar, Jenna; van der Lee, Sven J.; Joas, Erik; Wetterberg, Hanna; Hardy, John; Guerreiro, Rita; Bras, Jose; Waern, Margda; Kern, Silke; Zetterberg, Henrik; Blennow, Kaj; Skoog, Ingmar; et al.
Abstract: Introduction: Studies examining the effect of polygenic risk scores (PRS) for Alzheimer's disease (AD) and apolipoprotein E ( APOE ) genotype on incident dementia in very old individuals are lacking. Methods: A population‐based sample of 2052 individuals ages 70 to 111, from Sweden, was followed in relation to dementia. AD‐PRSs including 39, 57, 1333, and 13, 942 single nucleotide polymorphisms (SNPs) were used. Results: AD‐PRSs (including 39 or 57 SNPs) were associated with dementia (57‐SNPs AD‐PRS: hazard ratio 1.09, confidence interval 1.01–1.19, P  = .03), particularly in APOE ɛ4 non‐carriers (57‐SNPs AD‐PRS: 1.15, 1.05–1.27, P =  4 × 10 –3, 39‐SNPs AD‐PRS: 1.22, 1.10–1.35, P =  2 × 10 –4 ). No association was found with the other AD‐PRSs. Further, APOE ɛ4 was associated with increased risk of dementia (1.60, 1.35–1.92, P  = 1 × 10 –7 ). In those aged ≥95 years, the results were similar for the AD‐PRSs, while APOE ɛ4 only predicted dementia in the low‐risk tertile of AD‐PRSs. Discussion: These results provide information to identify individuals at increased risk of dementia.